Transformasi Spasial Rumah Limas berdasarkan Tipologi Bengkilas di Kawasan Sungai Musi - Ahmad Malik Abdul Aziz; Ibnu Aziz; Agustina E. Marzuki (Universitas Sebelas Maret Surakarta, 2026)
Spatial Transformation of Limas Houses Based on Bengkilas Typology along the Musi RiverLimas houses are a distinctive architectural heritage of Palembang characterized by the bengkilas system that forms spatial hierarchy. Their existence is closely related to the role of the Musi River in shaping riverside settlement patterns and community activities. However, urbanization, shifts in mobility orientation, and increasing demand for productive spaces have driven spatial transformations in limas houses. This study aims to analyze spatial transformation patterns of three- and four-bengkilas limas houses and their relationship with river-based community activities. This research employs a qualitative architectural typological analysis through literature review and visual documentation to examine spatial configurations and transformations. The results indicate major changes in underfloor use, bengkilas simplification, building orientation, and the use of modern materials affecting traditional spatial characteristics. This study recommends an adaptive preservation approach based on typology to support sustainable conservation of limas houses.